Screening genes encoding protein protease inhibitor from metagenome of sponge-associated microorganisms in Quang Tri sea, Vietnam - Hong, Tran Thi; Cuong, Pham Viet; Cuc, Nguyen Thi Kim (Academia Journal of Biology, 2019)
Using metagenomics-based method to isolate new compounds from the marine environment are getting more and more attention in recent years. Based on metagenome library, bioinformatics methods is a powerful tool for screening genes with new biological activities from uncultured microorganisms and become a breakthrough in research and application of biotechnology. In this study we selected and used the samples DNA QT2 which had high DNA content and purity from a total of 6 DNA samples of sponge-associated microorganisms collected in Quang Tri sea (Vietnam) for metagenomic sequencing (DNA concentration is 202.5 ng, A260/ A280 value is 1.80). 16S rRNA metagenomic sequencing data of QT2 produced 44,117,722 reads, which were assembled into 120,236 contigs. ORF prediction using Prodigal produced 386,416 ORFs. Functional annotation was conducted based on 7 different databases (NR, COG, CAZy, Swissprot, GO, KEGG, Pfam), and there are 266,553 genes were annotated using Swiss-Prot. In addition, based on the obtained metagenomic data, 50 complete genes encoding protease inhibitor proteins were revealed and among them, 28 genes encoding protein (> 50%) belonged to the serine protease inhibitor family, and 22 genes genes encoding belonged to the Inter-alpha-trypsin inhibitor group. NCBI BLAST screening results that these proteins had higher 50% identity to protease inhibitors.